THE EFFECT OF EMPTY FRUIT BUNCH AS GROWING MEDIA ON PRODUCTION AND PHYSICAL CHARACTERISTIC OF VOLVARIA VOLVACEAE - Budiyanto Budiyanto; Hafiza Fadhila (Jurnal Agroindustri, 2018)
Utilization of  palm oil empty fruit bunch (EFB) as a medium to grow mushroom can be one of the alternative utilization of oil palm biomass valley.  The  objective of the study was to evaluate EFB as a medium for growing mushroom (Volvariella volvacea).  In this study, two age variations of EFB and 3 media thickness variations were used to assess the characteristics of mushroom production, and to determine the quality of  harvested mushroom  based on SNI 01-6945-2003. The results showed that empty palm oil bunches for the best growth medium of mushroom (Volvariella volvacea), based on the total weight of mushroom, longest harvest time, and biological efficiency was the medium of empty palm fruit bunches of 6 weeks old with  medium thickness of 20 cm. In addition, the same media thickness of 20 cm of 5 and 6 weeks EFB can produce the highest fruit body length and diameter ofmushroom.